On Some Interesting Problems of Control Systems - Laszlo Keviczky; Csilla Bányász (International Journal of Robotics and Control Systems, 2022)
The paper discusses some interesting mainly philosophical paradigms of the modelling and control areas, which are still partly unsolved and/or only partially studied.